2021
DOI: 10.1111/cen.14416
|View full text |Cite
|
Sign up to set email alerts
|

Progression to prediabetes or diabetes in young Korean women with polycystic ovary syndrome: A longitudinal observational study

Abstract: Objective To investigate changes in glycaemic status in women with polycystic ovary syndrome (PCOS). Design Longitudinal observational study. Patients Women with PCOS who underwent baseline and follow‐up screening tests for diabetes (n = 262). Four patients with type 2 diabetes (T2DM) at baseline and 6 patients who were taking drugs at the final follow‐up were excluded. Measurements Changes in glycaemic classification based on fasting glucose, haemoglobin A1c and oral glucose tolerance test. Results The median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 30 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…The studies were published 2010–2021 and performed in European [ 8 , 9 , 18 , 29 , 34 , 35 , 37 ], Northern American [ 31 , 32 ], Asian [ 26 , 28 , 30 , 33 ], and Oceanic [ 25 , 27 ] study cohorts. No study was conducted in Southern American or African study cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published 2010–2021 and performed in European [ 8 , 9 , 18 , 29 , 34 , 35 , 37 ], Northern American [ 31 , 32 ], Asian [ 26 , 28 , 30 , 33 ], and Oceanic [ 25 , 27 ] study cohorts. No study was conducted in Southern American or African study cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of studies included in this review are outlined in Table 1. Seven of the studies were conducted in the United States, 27,36,39–41,44,56 six in Italy, 29–31,38,48,49 three studies in Iran, 26,45,50 three in Sweden 37,51,52 and each of the remaining 12 studies were conducted in Australia, 53 the Netherlands, 28 Denmark, 54 Turkey, 32 Bosnia, 55 Thailand, 46 Venezuela, 43 Spain and Germany, 35 Croatia, 34 Poland, 42 Korea 33 and Hong Kong 47 …”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies reported change in BMI, 28–32,34,35,37,39,40,42,47,49,50,52–54 10 studies reported changes in lipid profiles, 26,29,34,40,42,44,47–50,52,54,56 10 studies described HTN, 26,40,42,44,47,48,50,52,54,56 T2DM risk was reported by 11 studies 27,32,33,36,38,45–47,50,55,56 and 15 studies reported IR and/or IGT 28,29,31,32,34,36,40,42–44,47,48,50,52,54 . The majority of investigators described more than two outcomes, which explains the overlap in a number of studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of type 2 diabetes in women with PCOS is significantly increased regardless of age (odds ratio, 2.87; 95% confidence interval, 1.44–5.72) compared to women without PCOS, and this relationship is independent of, yet exacerbated by, obesity [ 12 ]. The prevalence of type 2 diabetes in young Korean women with PCOS (mean age, 24.7±5.8 years) was 3.0% (27/899) in our recent study [ 13 ], whereas that of the young population (15,050 women aged 20–29 years) in the Korean National Health Insurance Database was 0.3% [ 14 ]. Moreover, the incidence rate of type 2 diabetes was 9.3 per 1,000 person-years in women with PCOS, which was significantly higher ( p <0.0001) than that of the overall population of women aged 20–29 years (0.9 per 1,000 person-years).…”
Section: Managementmentioning
confidence: 99%